Impact of oral calcium on mortality of dialysis patients - an underestimated risk? - Bommer, Jürgen; Ritz, Eberhard (Nephrology, dialysis, transplantation, 2012)
© The Author 2012. Published by Oxford University Press on behalf of ERA-EDTA. All rights reserved. For Permissions, please e-mail: journals.permissionsoup.comcalcification, calcium, haemodialysis, phosphate, phosphate binder...Phosphate is an accepted trigger and promoter of soft tissue calcification. Today, oral calcium-containing phosphate binders are still frequently administered to reduce hyperphosphataemia in patients with reduced renal function. There is, however, increasing evidence that a positive calcium balance and elevated serum calcium concentrations may aggravate soft tissue calcification. Some recent controlled [1, 2] trials as well as recent unpublished observational evidence from Dialysis Outcome and Practice Pattern Study (DOPPS) point to increased mortality in renal patients treated with calcium-containing P binders. Unfortunately, each of these studies has some methodological limitations. Nevertheless, a recent meta-analysis documented an increased risk of myocardial infarction and stroke even in patients without kidney disease when treated with calcium supplements [...
Gesehen am 05.04.2018